Implementation of E-Government at The Bali Police Command Center as a Control Center for the Implementation of Personnel Duties - Wiradiputra, Dewa Gede Angga; Subawa, Nyoman Sri (Green Publisher Indonesia, 2025)
The Bali Police 110 Call Center service is provided to provide fast service to the public by utilizing information technology. This service has been regulated in Perpol No. 1 of 2018, through this service the public can make complaints/reports quickly and anywhere. This study was conducted to measure the level of service effectiveness, the realization of successful e-government elements in the development of these services, and to determine the inhibiting factors of the service. The research method used in this study is qualitative with data collection techniques in the form of interviews, observations, and documentation studies. The results of this study indicate that the 110 Call Center service cannot be said to be effective, because it has not been able to achieve program targets which cause the input level to be greater than the output. The factors that support this Call Center service to survive until now are the support provided by various parties so that this service can be disseminated. The existence of capacity in the form of budget availability, facilities, and human resources in its operation. As well as the existence of good value or benefits that can be utilized by service recipients. In addition, the inhibiting factors that make this service ineffective are the lack of public understanding of this service, as well as the less than optimal form of socialization carried out by the Bali Police to community groups regarding this 110 Call Center service.